A relocalização produtiva da indústria de calçados e a análise da participação das aglomerações produtivas calçadistas na cadeia global do setor - Fernandes, Lívia Socorro de Castro (2010)
Agglomerations of firms are able to provide external economies to producers, providing them increase their competitiveness. However, it is important to understand how these local agglomerations participate in broader contexts such as national and international. And how is integration and the participation of companies in global commodity chains. In this work, it is presented a conceptual discussion about the competitive advantages of the firms in industrial clusters and the conformation of the global commodity chains, analyzes the behavior of exports of footwear from Brazil and the Northeast and analyzes that the Brazilian footwear sector is subordinate to the interests of international buyers are responsible for leading the global chain. The northeast is important exporter of footwear, so it is included in this global chain.